2006
DOI: 10.1161/01.atv.0000198239.41189.5d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cardiovascular Risk Factors on Endothelial Progenitor Cells

Abstract: Abstract-The ideal way to prevent and cure atherosclerosis and the subsequent end organ damage is to restore and rejuvenate the dysfunctional vasculature and the damaged organs. Various studies have underlined the important role of bone marrow-derived endothelial progenitor cells (EPCs) in vasculogenesis and angiogenesis of ischemic tissue, but only a few studies have concentrated on the role of EPCs in the prevention and therapy of atherosclerosis. Extended endothelial cell damage by cardiovascular risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(179 citation statements)
references
References 103 publications
6
168
0
5
Order By: Relevance
“…7,18 Human PROM1 is expressed by various stem and progenitor cells originating from diverse sources. 23 Owing to the role of EPCs in vascular and endothelial function, 24 we investigated these characteristics in five carriers of the R373C mutation. We found that the number of CECs, endothelial markers such as CD133, as well as the ability of EPCs to form endothelial colonies fell within the normal range in the tested patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,18 Human PROM1 is expressed by various stem and progenitor cells originating from diverse sources. 23 Owing to the role of EPCs in vascular and endothelial function, 24 we investigated these characteristics in five carriers of the R373C mutation. We found that the number of CECs, endothelial markers such as CD133, as well as the ability of EPCs to form endothelial colonies fell within the normal range in the tested patients.…”
Section: Discussionmentioning
confidence: 99%
“…The transplant was created by injecting 5ϫ10 6 BM cells into the lateral tail vein of lethally irradiated (1100 rads) mouse recipients.…”
Section: Bm Isolation and Transplantationmentioning
confidence: 99%
“…Inserts were placed over 24-well plates coated with a thin layer of 1% agarose in 1ϫ PBS to facilitate removal of transmigrated cells for further analysis. Freshly isolated BM cells (2ϫ10 6 ) from WT or FSP-1-GFP ϩ mice were added to the top chamber and allowed to transmigrate through HUVEC at 37°C. After 3 or 24 hours, the top chamber was removed and the cell number in the bottom chamber was determined using a Z1 Beckman Coulter counter (Beckman Coulter, Fullerton, CA) GFP ϩ cells were counted using fluorescent microscope.…”
Section: Transendothelial Migration and Invasion Assaymentioning
confidence: 99%
See 2 more Smart Citations